Libra - Concept and Policy Implications - Jonas Groß; Bernhard Herz; Jonathan Schiller (Universität Bayreuth, 2019)
The announcement of the Libra Association to issue a private global currency has triggered a heated debate about the concomitantadvantages and risks. Proponents expectLibra to unfetter money from its "governmental chains" and liberalize and cheapen monetary transactions around the globe. Opponents argue that a private currency imposes unforeseeable risks forboth individualsand the whole financial system. Furthermore, Libra could hamper monetary policies of national central banks. This paper contributes to the debate in two ways. First, we offer a comprehensive overview of the concept of Libra and its possible benefits and downsides to analyze its market potential. Second, we discuss potential implications that a private currency as Libra poses for monetary policy and financial regulation.
Keywords: E42; E52; G28; 330; Libra; Cryptocurrency; Monetary Policy; Currency Regime